2023
DOI: 10.3390/plants12173168
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory and Antiproliferative Effects of Osmanthus fragrans (Thunb.) Lour. Flower Extracts

Steven Kuan-Hua Huang,
Paolo Robert P. Bueno,
Patrick Jay B. Garcia
et al.

Abstract: Osmanthus fragrans (Thunb.) Lour. flowers (OF-F) have been traditionally consumed as a functional food and utilized as folk medicine. This study evaluated the antioxidant, anti-inflammatory and cytotoxic effects of OF-F extracts on prostate cancer cells (DU-145) and determined possible protein-ligand interactions of its compounds in silico. The crude OF-F extracts—water (W) and ethanol (E) were tested for phytochemical screening, antioxidant, anti-inflammatory, and anti-cancer. Network and molecular docking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…In addition, the floral aroma of O. fragrans has been found to directly inhibit appetite neuropeptides in the hypothalamus, which can contribute to reducing food intake and ultimately aiding in weight management [30]. It was shown that intragastric administration of cinnamon extract to mice for 15 consecutive days effectively inhibited acetaminopheninduced elevation of glutamine aminotransferase, ameliorated lipid peroxidation in the liver and lungs, and significantly reduced vacuolization in liver tissue [31]. Loganic acid, a major secondary metabolite of O. fragrans, reduces the expression of key lipogenesis-related genes, such as lipocalin and lipoprotein lipase, and has anti-adipogenic and anti-osteoporotic effects [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the floral aroma of O. fragrans has been found to directly inhibit appetite neuropeptides in the hypothalamus, which can contribute to reducing food intake and ultimately aiding in weight management [30]. It was shown that intragastric administration of cinnamon extract to mice for 15 consecutive days effectively inhibited acetaminopheninduced elevation of glutamine aminotransferase, ameliorated lipid peroxidation in the liver and lungs, and significantly reduced vacuolization in liver tissue [31]. Loganic acid, a major secondary metabolite of O. fragrans, reduces the expression of key lipogenesis-related genes, such as lipocalin and lipoprotein lipase, and has anti-adipogenic and anti-osteoporotic effects [32,33].…”
Section: Introductionmentioning
confidence: 99%